Cytomegalovirus viremia predicts postdischarge mortality in Kenyan HIV-exposed uninfected children - Pavlinac, PB; Singa, B; Huang, M-L; Berkley, JA (Oxford University Press, 2023)
Background Cytomegalovirus (CMV) viremia is associated with mortality in severely ill immunocompetent adults and hospitalized children with HIV (CWH). We measured CMV viremia in HIV-exposed and -unexposed Kenyan children aged 1–59 months discharged from hospital and determined its relationship with postdischarge mortality.